Competitiveness and Innovation of Enterprises of the SME Sector in Poland - Janas, Mateusz (Studies of the Industrial Geography Commission of the Polish Geographical Society, 2019)
In the 21st century economy, referred to as the knowledge-based economy (KBE), the competitiveness of a business and its position depends, to a large extent, on innovations in the products and services it offers. In the EU countries, the entities that are referred to as its “driving force” are businesses belonging to the SME sector (small and medium sized enterprises). Therefore, the subject matter of this study is the competitiveness and the innovativeness of those enterprises in Poland after the country’s accession to the EU structures, i.e. after 2004. The paper discusses the very notion of innovativeness and competitiveness of a business, pointing to the factors shaping the influence of innovation on its competitive position. The realisation of changes that are connected with the innovative activity of a businesses is understood as the ability to implement improvements regarding products, processing, marketing and organisation. The paper presents the types of innovations, as well as their possible effects that affect the position of a business on the competitive market that is changing dynamically.